Kinematics of an origami inspired millipede robot - Liu, C; You, Z; Maiolino, P (American Society of Mechanical Engineers, 2022)
A millipede is a worm-like arthropod with a relatively hard exoskeleton, a segmented body, and numerous pairs of legs. Its appendage helps to coordinate the behaviour of multiple body segments to generate a peristaltic wave, so that efficient locomotion can be achieved on uneven surfaces and limited space. When sensing danger or disturbed, the millipede curls up into a coil shape to protect itself against predators. The curling behaviour of a millipede has also been found in some of its close relatives in the arthropod family, such as pill bugs and lobsters. Inspired by its peristaltic and curling behaviours, we propose an origami-based concept for a robot that imitates the motion of a millipede. The mechanism is made with a chain of interlinked modules, mimicking the segments in a millipede. Each module is an assembly of rigid facets with a uniform and finite thickness, reducing the overall degrees of freedom (DoF) to a manageable number. Given its unique geometric design, the assembly can contain any number of modules without an excessively large DoF. Its curling and peristaltic motions are quantified kinematically in the paper, which paves the way for the millipede robot design with actuation and control components integrated. In addition, a few other configurations of the proposed origami mechanism and its geometric variants are presented, thus opening up design space for other possible applications.